Carbon aerogel as well as preparation method and application thereof
By adjusting the ratio and mass fraction of resorcinol and formaldehyde in the precursor solution, combined with atmospheric drying and carbonization treatment, the existing carbon aerogel preparation methods are solved with complex process, high cost and poor electrochemical performance. Problem, low-cost, high-performance carbon aerogel is prepared.
Patent Information
- Application Number
- CN202411674879.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing carbon aerogel preparation methods have problems such as complex preparation process, high production cost and poor electrochemical performance, especially during normal pressure drying, which can easily lead to skeleton damage and low electrochemical performance.
By adjusting the molar ratio and mass fraction of resorcinol to formaldehyde in the precursor solution and drying atmospheric pressure without adding a modifier, ensuring that the strength of the organic wet gel can resist structural collapse during the drying process , and finally, high-performance carbon aerogel is prepared by carbonization.
It achieves low preparation cost, simple process, and excellent electrochemical properties of carbon aerogel, which is suitable for use as an electrode material for supercapacitors.
Smart Images

Figure CN119503772A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrode materials, and in particular relates to a carbon aerogel and a preparation method and application thereof. Background Art
[0002] As an emerging electronic component, supercapacitors have high power density and excellent energy output performance, which effectively make up for the defect of insufficient energy density of traditional capacitors. Compared with batteries, supercapacitors have the advantages of fast charging and discharging speed and long cycle life. In recent years, supercapacitors have developed rapidly as an advanced energy storage device and are widely used in public transportation, industrial production, consumer electronics, aerospace and other fields.
[0003] Electrode material is one of the key factors affecting the performance of supercapacitors. Carbon aerogel is considered to be a high-performance electrode material that can be used to prepare supercapacitors due to its rich pore structure, high specific surface area and good conductivity.
[0004] In the preparation process of carbon aerogel, the drying effect of organic wet gel has a great influence on the performance of carbon aerogel products. The purpose of drying organic wet gel is to remove the solvent (usually water) in the organic wet gel so that the pores in the gel structure are filled with air to obtain organic aerogel. The organic aerogel is then carbonized to prepare carbon aerogel.
[0005] Generally, there are two drying methods for organic wet gels: supercritical drying and atmospheric pressure drying. Among them, the technical solutions involved in the three patent documents with application numbers CN01126015.7, CN01126016.5, and CN200610116392.3 all use supercritical drying to prepare carbon aerogels. Although supercritical drying can effectively avoid the structural collapse of organic wet gels during the drying process, the carbon aerogels finally prepared can effectively inherit the rich pore structure in the organic wet gels. However, the reaction conditions of supercritical drying are harsh, the equipment requirements are high, and the energy consumption is very large during the drying process, which will greatly increase the preparation cost of carbon aerogels. Obviously, supercritical drying is not suitable for large-scale production of carbon aerogels. In contrast, atmospheric pressure drying does not require the addition of additional drying equipment, and its energy consumption during the drying process is low, which greatly reduces the preparation cost of carbon aerogels. However, during the atmospheric pressure drying process, due to the presence of liquid surface tension, the pore structure of the organic wet gel is extremely easy to be destroyed, which will affect the performance of the carbon aerogel finally prepared. In order to solve this problem, it is generally chosen to add a modifier to the precursor solution to enhance the strength of the organic wet gel and to reduce the surface tension of the liquid phase by solvent replacement before drying to achieve normal pressure drying. Among them, application numbers CN201710238793.4, CN202010295048.5, and CN 201610222935.3 use sodium 4-hydroxybenzenesulfonate, polymer F127, and ascorbic acid (VC) as modifiers, respectively, and after the organic wet gel is prepared, the solvent is replaced, and then it is dried at normal pressure. Among them, solvent replacement is to immerse the organic wet gel in a solvent with lower surface tension (ethanol, acetone, etc.). During this process, the water in the organic wet gel will be replaced by the solvent with lower surface tension. This process needs to last for 3 to 7 days, and the solvent required for replacement needs to be continuously replaced during the process. There is no doubt that solvent replacement will prolong the preparation time of carbon aerogel and cause a large amount of waste of replacement solvent. This undoubtedly hinders the application of normal pressure drying in the preparation of carbon aerogel. Of course, in order to avoid the solvent replacement required before normal pressure drying, some methods are to dissolve the precursor in a low surface tension solvent and gel therein so that the solvent in the organic wet gel is a surface tension solvent, so as to achieve normal pressure drying without solvent replacement. Among them, the patent paper with application number CN03139852.9 mentioned that hexamethylenetetramine can be used as a coagulant to gel in a low surface tension solvent (isopropanol, methanol, etc.) to form an organic wet gel, and then the organic wet gel is directly dried at normal pressure.In addition, the patent paper with application number CN200410027355.6 also mentioned that surfactants (hexadecyl trimethylammonium bromide, sodium dodecyl sulfate) can be used in the precursor solution to reduce the surface tension of the solvent system, so that the solvent surface tension in the organic wet gel obtained after gelation is lower, so as to directly dry the organic wet gel at normal pressure. However, the addition of these additional additives will consume the active sites of the precursor solution during the gel polymerization reaction, which will lead to insufficient polymerization reaction, thereby adversely affecting the performance of the finally prepared carbon aerogel, which is obviously not conducive to the subsequent use of carbon aerogel as a supercapacitor capacitance material. In the patent document with application number CN200410027355.6, the method of adding graphite-like microcrystals as additives avoids solvent replacement while not adversely affecting the electrochemical properties of the final product. However, the synthesis of such graphite-like microcrystals adds additional steps to the entire preparation process.
[0006] Considering that carbon aerogels used in supercapacitors have special requirements for their electrochemical properties, and many patents involving the preparation of carbon aerogels by atmospheric pressure drying have not effectively evaluated the electrochemical properties, and the important electrochemical parameters of carbon aerogels used as supercapacitors in a few patents are also low. In summary, the existing preparation methods of carbon aerogels still have problems such as complex preparation processes, high production costs, and most of the carbon aerogels prepared are not suitable for use as supercapacitor electrode materials. Summary of the invention
[0007] In order to solve the above problems in the prior art, the present invention provides a carbon aerogel and a preparation method and application thereof. The carbon aerogel provided by the present invention has low preparation cost, simple preparation process, good electrochemical performance, and is suitable for use as an electrode material for supercapacitors.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] The present invention provides a method for preparing carbon aerogel, comprising the following steps:
[0010] (1) Preparation of precursor solution: adding resorcinol and formaldehyde into water to obtain a precursor solution;
[0011] (2) gelation and aging reaction: subjecting the precursor solution obtained in step (1) to a gelation reaction, and after a period of time, aging the gel to obtain an organic wet gel;
[0012] (3) Drying the organic wet gel: drying the organic wet gel obtained in step (2) at normal pressure to obtain an organic aerogel;
[0013] (4) Carbonization treatment: The organic aerogel obtained in step (3) is carbonized to obtain the carbon aerogel.
[0014] As a preferred technical solution of the present invention, in step (1), the molar ratio of resorcinol to formaldehyde is 1:(1.5-2.5), and the sum of the mass fractions of resorcinol and formaldehyde in the precursor solution is 35-45%. By increasing the mass concentration of the reactants in the precursor solution, the packing density of microscopic particles in the internal structure of the organic wet gel formed after the gelation and aging steps is increased to ensure that the organic wet gel can avoid the skeleton destruction in its internal microstructure caused by the normal pressure drying process, and at the same time ensure that the finally prepared carbon aerogel can be well used as an electrode material in supercapacitors.
[0015] As a preferred technical solution of the present invention, a catalyst sodium carbonate is also added to the precursor solution in step (1), and the added amount does not exceed 1 / 2000 of the molar amount of resorcinol. The catalyst sodium carbonate is added to the precursor solution to adjust the gel reaction of the solution to ensure that the strength of the formed organic wet gel can resist the structural collapse caused by the liquid phase surface tension during the normal pressure drying process, and to achieve this purpose, it is necessary to ensure that the added amount of the catalyst does not exceed 1 / 2000 of the molar amount of resorcinol.
[0016] As a preferred technical solution of the present invention, in step (2), the gelling and aging temperatures are both 40 to 100° C., the gelling reaction time is 8 to 20 hours, and the aging time is 20 to 60 hours.
[0017] As a preferred technical solution of the present invention, in step (3), the normal pressure drying temperature is 50 to 100° C. and the time is 24 to 48 hours.
[0018] As a preferred technical solution of the present invention, in step (4), the carbonization is carried out under an inert atmosphere, and the specific operation is: heating to 700-1300° C. at 1-5° C. / min and keeping the temperature for 1-5 h.
[0019] The present invention also provides a carbon aerogel prepared according to the above-mentioned method for preparing the carbon aerogel.
[0020] The present invention also provides an application of the carbon aerogel described above in a supercapacitor.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) In the process of preparing carbon aerogels of the present invention, the drying of organic wet gels only needs to be carried out under normal pressure, which will save the equipment investment required for supercritical drying, simplify the preparation process of carbon aerogels, reduce energy consumption during the preparation process, and greatly reduce the preparation cost of carbon aerogels. In addition, before normal pressure drying, the organic wet gel does not need to be solvent replaced, which makes the preparation process of carbon aerogels simpler, greatly improves production efficiency, and does not cause a large amount of solvent waste.
[0023] (2) The carbon aerogel of the present invention has a low shrinkage rate during the normal pressure drying process, which can effectively avoid the skeleton collapse problem caused by the liquid phase surface tension during the normal pressure drying process of the carbon aerogel. The specific surface area of the prepared carbon aerogel is 500 to 700 m 2 / g, density is 0.5~0.7g / cm 3 .
[0024] (3) The method of the present invention does not require the use of modifiers or additives that may affect the purity and electrochemical properties of the carbon aerogel in the technical route of achieving normal pressure drying of organic wet gels. The prepared carbon aerogel has an ash content of less than 0.1% and an electrical conductivity of >15S / cm. Its specific capacity is 140-180F / g. After 2000 cycles at a current density of 5A / g, the capacity retention rate is 95-99%, and the electrochemical performance is excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 This is a morphology picture of the carbon aerogel prepared in Example 1;
[0027] Figure 2 This is the nitrogen adsorption-desorption curve of the carbon aerogel prepared in Example 1;
[0028] Figure 3 This is a morphology picture of the carbon aerogel prepared in Example 2;
[0029] Figure 4 This is the nitrogen adsorption-desorption curve of the carbon aerogel prepared in Example 2;
[0030] Figure 5 This is a morphology picture of the carbon aerogel prepared in Example 3;
[0031] Figure 6 This is the nitrogen adsorption-desorption curve of the carbon aerogel prepared in Example 3;
[0032] Figure 7 This is the morphology of the carbon aerogel prepared in Example 4;
[0033] Figure 8 This is the nitrogen adsorption-desorption curve of the carbon aerogel prepared in Example 4.
[0034] Fig. 9 This is the morphology of the carbon aerogel prepared in Example 5;
[0035] Fig.10 This is the nitrogen adsorption-desorption curve of the carbon aerogel prepared in Example 5.
[0036] Fig.11 This is the morphology of the carbon aerogel prepared in Comparative Example 1;
[0037] Fig.12 This is the nitrogen adsorption-desorption curve of the carbon aerogel prepared in Comparative Example 1.
[0038] Fig.13 This is the morphology of the carbon aerogel prepared in Comparative Example 2;
[0039] Fig.14 This is the nitrogen adsorption-desorption curve of the carbon aerogel prepared in Comparative Example 2.
[0040] Fig.15 This is the morphology of the carbon aerogel prepared in Comparative Example 3;
[0041] Fig.16 This is the nitrogen adsorption-desorption curve of the carbon aerogel prepared in Comparative Example 3. DETAILED DESCRIPTION
[0042] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0043] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0044] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0045] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0046] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0047] In the following examples, normal pressure refers to the range of 84-108 KPa; the raw materials used in the following examples are all commercially available conventional raw materials, and are not particularly limited. The following description will not be repeated.
[0048] Example 1
[0049] The preparation steps of carbon aerogel are as follows:
[0050] 11 g of resorcinol, 16.2 ml of formaldehyde and 20 ml of deionized water were weighed respectively and placed in an 80 ml columnar glass container, and stirred on a magnetic stirrer. After the resorcinol was completely dissolved and mixed evenly, the glass container was sealed and placed in an oven at 50°C for gel reaction for 20 hours, and then the oven temperature was adjusted to 70°C, and an aging operation was performed for 50 hours to obtain an organic wet gel; the organic wet gel was placed in an oven at 100°C and dried at normal pressure for 24 hours to obtain an organic aerogel; the organic aerogel was placed in a tubular furnace, and the temperature was increased to 900°C at a heating rate of 3°C / min under the protection of a nitrogen atmosphere, and the temperature was kept for carbonization for 4 hours. After cooling to room temperature, it was ground and passed through a 200-mesh sieve to obtain a carbon aerogel.
[0051] In the precursor solution of this embodiment, the mass fraction of resorcinol and formaldehyde is 36%, and no catalyst is added. The morphology of the prepared carbon aerogel material is as follows: Figure 1 As shown by Figure 1 It can be seen that the carbon aerogel prepared in this example has a good skeleton and has not collapsed; its shrinkage rate during the normal pressure drying process is 8%. Figure 2 As shown, its specific surface area is 614m2 / g; the electrochemical performance test shows that its specific capacity is 162F / g. The conductivity of the carbon aerogel material is 16.3S / cm, showing excellent conductivity. At the same time, its capacity retention rate reaches 98% after 2000 cycles at a current density of 5A / g, showing high cycle stability.
[0052] Example 2
[0053] The preparation steps of carbon aerogel are as follows:
[0054] 11 g of resorcinol, 16.2 ml of formaldehyde, 0.0053 g of sodium carbonate, and 15.3 ml of deionized water were weighed respectively and placed in an 80 ml columnar glass container, and stirred on a magnetic stirrer. After the resorcinol and sodium carbonate were completely dissolved and mixed evenly, the glass container was sealed and placed in a 70° C. oven for gel reaction for 16 hours, and then the oven temperature was adjusted to 80° C., and an aging operation was performed for 40 hours to obtain an organic wet gel; the organic wet gel was placed in an 80° C. oven and dried at normal pressure for 36 hours to obtain an organic aerogel; the organic aerogel was placed in a tubular furnace, and the temperature was increased to 1050° C. at a heating rate of 1° C. / min under the protection of an argon atmosphere, and the temperature was kept for carbonization for 1 hour. After cooling to room temperature, it was ground and passed through a 200-mesh sieve to obtain a carbon aerogel.
[0055] In the precursor solution of this embodiment, the mass fraction of resorcinol and formaldehyde is 40%, and the molar ratio of the catalyst sodium carbonate to resorcinol is 1:2000. The morphology of the prepared carbon aerogel material is shown in FIG. Figure 3 As shown by Figure 3 It can be seen that the carbon aerogel prepared in this example has a good skeleton and does not collapse; its shrinkage rate during the normal pressure drying process is 12%. The nitrogen adsorption and desorption curve of the carbon aerogel is shown in Figure 4 As shown, its specific surface area is 575m 2 / g; the electrochemical performance test shows that its specific capacity is 155F / g. The conductivity of the carbon aerogel material is 27.6S / cm, showing excellent conductivity. At the same time, its capacity retention rate reaches 96% after 2000 cycles at a current density of 5A / g, showing high cycle stability.
[0056] Example 3
[0057] The preparation steps of carbon aerogel are as follows:
[0058] 11 g of resorcinol, 16.2 ml of formaldehyde, 0.00106 g of sodium carbonate, and 17.5 ml of deionized water were weighed respectively and placed in an 80 ml columnar glass container, and stirred on a magnetic stirrer. After the resorcinol and sodium carbonate were completely dissolved and mixed evenly, the glass container was sealed and placed in a 40° C. oven for gel reaction for 20 hours, and then the oven temperature was adjusted to 60° C., and an aging operation was performed for 60 hours to obtain an organic wet gel; the organic wet gel was placed in a 90° C. oven and dried at normal pressure for 30 hours to obtain an organic aerogel; the organic aerogel was placed in a tubular furnace, and the temperature was increased to 950° C. at a heating rate of 2° C. / min under the protection of a nitrogen atmosphere, and the temperature was kept for carbonization for 2 hours. After cooling to room temperature, it was ground and passed through a 200-mesh sieve to obtain a carbon aerogel.
[0059] In the precursor solution of this embodiment, the mass fraction of resorcinol and formaldehyde is 38%, and the molar ratio of the catalyst sodium carbonate to resorcinol is 1:10000. The morphology of the prepared carbon aerogel material is shown in FIG. Figure 5 As shown by Figure 5 It can be seen that the carbon aerogel prepared in this example has a good skeleton and does not collapse; its shrinkage rate during the normal pressure drying process is 6%. Figure 6 As shown, its specific surface area is 499m 2 / g; the electrochemical performance test shows that its specific capacity is 172F / g. The conductivity of the carbon aerogel material is 18.5S / cm, showing excellent conductivity. At the same time, its capacity retention rate reaches 97% after 2000 cycles at a current density of 5A / g, showing high cycle stability.
[0060] Example 4
[0061] The preparation steps of carbon aerogel are as follows:
[0062] 11 g of resorcinol, 16.2 ml of formaldehyde, and 0.00212 g of sodium carbonate were weighed respectively, and 13.2 ml of deionized water was added and placed in an 80 ml columnar glass container, and stirred on a magnetic stirrer. After the resorcinol and sodium carbonate were completely dissolved and mixed evenly, the glass container was sealed and placed in an oven at 60° C. for gel reaction for 18 hours, and then the oven temperature was adjusted to 80° C., and an aging operation was performed for 40 hours to obtain an organic wet gel; the organic wet gel was placed in an oven at 65° C. and dried at normal pressure for 36 hours to obtain an organic aerogel; the organic aerogel was placed in a tubular furnace, and the temperature was increased to 850° C. at a heating rate of 4° C. / min under the protection of a nitrogen atmosphere, and the temperature was kept for carbonization for 4 hours. After cooling to room temperature, it was ground and passed through a 200-mesh sieve to obtain a carbon aerogel.
[0063] In the precursor solution of this embodiment, the mass fraction of resorcinol and formaldehyde is 42%, and the molar ratio of the catalyst sodium carbonate to resorcinol is 1:5000. The morphology of the prepared carbon aerogel material is shown in FIG. Figure 7 As shown by Figure 7 It can be seen that the carbon aerogel prepared in this example has a good skeleton and does not collapse; its shrinkage rate during the normal pressure drying process is 9%. Figure 8 As shown, its specific surface area is 689m 2 / g; the electrochemical performance test shows that its specific capacity is 166F / g. The conductivity of the carbon aerogel material is 15.3S / cm, showing excellent conductivity. At the same time, its capacity retention rate reaches 95% after 2000 cycles at a current density of 5A / g, showing high cycle stability.
[0064] Example 5
[0065] The preparation steps of carbon aerogel are as follows:
[0066] 11 g of resorcinol, 16.2 ml of formaldehyde, 0.0021 g of sodium carbonate, and 20 ml of deionized water were weighed respectively and placed in an 80 ml columnar glass container, and stirred on a magnetic stirrer. After the resorcinol was completely dissolved and mixed evenly, the glass container was sealed and placed in an oven at 50°C for gel reaction for 20 hours, and then the oven temperature was adjusted to 70°C, and an aging operation was performed for 50 hours to obtain an organic wet gel; the organic wet gel was placed in an oven at 100°C and dried at normal pressure for 24 hours to obtain an organic aerogel; the organic aerogel was placed in a tubular furnace, and the temperature was increased to 900°C at a heating rate of 3°C / min under the protection of a nitrogen atmosphere, and the temperature was kept for carbonization for 4 hours. After cooling to room temperature, it was ground and passed through a 200-mesh sieve to obtain a carbon aerogel.
[0067] The difference between this embodiment and embodiment 1 is that the catalyst sodium carbonate is further added in this embodiment, and the molar ratio of sodium carbonate to resorcinol is 1:5000. The morphology of the prepared carbon aerogel material is as follows: Fig. 9 As shown by Fig.10 It can be seen that the carbon aerogel prepared in this example has a good skeleton and does not collapse; its shrinkage rate during the normal pressure drying process is 6%. Fig.10 As shown, its specific surface area is 687m 2 / g; the electrochemical performance test shows that its specific capacity is 173F / g. The conductivity of the carbon aerogel material is 42.8S / cm, showing excellent conductivity. At the same time, its capacity retention rate reaches 99% after 2000 cycles at a current density of 5A / g, showing high cycle stability. In addition, the various properties of the carbon aerogel prepared in this embodiment are better than those in Example 1.
[0068] Comparative Example 1
[0069] The preparation steps of carbon aerogel are as follows:
[0070] 11 g of resorcinol, 16.2 ml of formaldehyde, and 0.021 g of sodium carbonate were weighed respectively and added with 20 ml of deionized water and placed in an 80 ml columnar glass container, which was placed on a magnetic stirrer for stirring. After the resorcinol and sodium carbonate were completely dissolved and mixed evenly, the glass container was sealed and placed in an oven at 50° C. for gel reaction for 20 hours, and then the oven temperature was adjusted to 70° C. and an aging operation was performed for 50 hours to obtain an organic wet gel; the organic wet gel was placed in an oven at 100° C. and dried at normal pressure for 24 hours to obtain an organic aerogel; the organic aerogel was placed in a tubular furnace, heated to 900° C. at a heating rate of 3° C. / min under the protection of a nitrogen atmosphere, and carbonized for 4 hours at a heat preservation temperature. After cooling to room temperature, it was ground and passed through a 200-mesh sieve to obtain a carbon aerogel.
[0071] The difference between this comparative example and Example 1 is that the amount of sodium carbonate catalyst added in this comparative example is very high. The morphology of the prepared carbon aerogel material is shown in FIG. Fig.11 As shown by Fig.11 It can be seen that the carbon aerogel skeleton prepared in this example has undergone severe shrinkage after being dried at normal pressure, and its internal structure has collapsed; its shrinkage rate during the normal pressure drying process is as high as 39%. Fig.12 As shown, it can be seen that its internal pores are mainly micropores and a small number of mesoporous structures. It can be seen that the abundant mesopores and macropores inside are severely damaged during the normal pressure drying process, which will affect its use as a supercapacitor electrode material. The electrochemical performance test shows that its specific capacity is only 96F / g, which is significantly different from the embodiment. The electrical conductivity of the carbon aerogel is 9.1S / cm, and its electrical conductivity is lower than that of the embodiment. At the same time, its capacity retention rate is 86% after 2000 cycles at a current density of 5A / g, and its cycle performance is significantly insufficient compared with the embodiment.
[0072] Comparative Example 2
[0073] The preparation steps of carbon aerogel are as follows:
[0074] 11 g of resorcinol and 16.2 ml of formaldehyde were weighed respectively, and 0.05 g of hexadecyltrimethylammonium bromide (CTAB) was added. 20 ml of deionized water was measured and placed in an 80 ml columnar glass container, and stirred on a magnetic stirrer. After the resorcinol and sodium carbonate were completely dissolved and mixed evenly, the glass container was sealed and placed in an oven at 50°C for gel reaction for 20 hours, and then the oven temperature was adjusted to 70°C, and an aging operation was performed for 50 hours to obtain an organic wet gel; the organic wet gel was placed in an oven at 100°C and dried at normal pressure for 24 hours to obtain an organic aerogel; the organic aerogel was placed in a tubular furnace, and the temperature was increased to 900°C at a heating rate of 3°C / min under the protection of a nitrogen atmosphere, and the temperature was kept for carbonization for 4 hours. After cooling to room temperature, it was ground and passed through a 200-mesh sieve to obtain a carbon aerogel.
[0075] The difference between this comparative example and Example 1 is that the modifier CTAB is added in this comparative example. The morphology of the prepared carbon aerogel material is shown in FIG. Fig.13 As shown by Fig.13 It can be seen that the carbon aerogel particles prepared in this example are very large in size, and their internal structure is very different from that of the carbon aerogel without adding a modifier; although its shrinkage rate during the atmospheric pressure drying process is only 8%, its internal pore structure is no longer suitable for use in supercapacitors. Fig.14 As shown, it can be seen that its internal pores are mainly microporous structures, which is not conducive to the passage of electrolytes inside it when used as a supercapacitor. The electrochemical performance test shows that its specific capacity is only 86F / g, which is significantly different from the embodiment. The conductivity of the carbon aerogel is 7.1S / cm, which is lower than that of the embodiment. At the same time, its capacity retention rate is 91% after 2000 cycles at a current density of 5A / g, and its cycle performance is significantly insufficient compared with the embodiment.
[0076] Comparative Example 3
[0077] The preparation steps of carbon aerogel are as follows:
[0078] 11 g of resorcinol and 16.2 ml of formaldehyde were weighed respectively, and 0.04 g of sodium hydroxide was added. 20 ml of deionized water was measured and placed in an 80 ml columnar glass container, and the container was placed on a magnetic stirrer for stirring. After the resorcinol and sodium carbonate were completely dissolved and mixed evenly, the glass container was sealed and placed in a 50° C. oven for gel reaction for 20 hours, and then the oven temperature was adjusted to 70° C., and an aging operation was performed for 50 hours to obtain an organic wet gel; the organic wet gel was placed in a 100° C. oven at normal pressure and dried for 24 hours to obtain an organic aerogel; the organic aerogel was placed in a tubular furnace, and the temperature was increased to 900° C. at a heating rate of 3° C. / min under the protection of a nitrogen atmosphere, and the temperature was kept for carbonization for 4 hours. After cooling to room temperature, it was ground and passed through a 200-mesh sieve to obtain a carbon aerogel.
[0079] The difference between this comparative example and Example 1 is that the catalyst sodium hydroxide is also added in this comparative example, wherein the molar ratio of sodium hydroxide to resorcinol is 1:100. The morphology of the prepared carbon aerogel material is shown in FIG. Fig.15 As shown by Fig.15 It can be seen that the carbon aerogel skeleton prepared in this example has undergone severe shrinkage after being dried at normal pressure, and its internal structure has collapsed; its shrinkage rate during the normal pressure drying process is as high as 43%. Fig.16 As shown, it can be seen that its internal pores are mainly micropores and a small number of mesoporous structures. The abundant mesopores and macropores inside are severely damaged during the normal pressure drying process due to the insufficient skeleton strength, which will affect its use as a supercapacitor electrode material. The electrochemical performance test shows that its specific capacity is 102F / g, which is significantly different from the embodiment. The electrical conductivity of the carbon aerogel is 12.1S / cm, and its electrical conductivity is lower than that of the embodiment. At the same time, its capacity retention rate is only 92% after 2000 cycles at a current density of 5A / g, and its cycle performance is significantly insufficient compared with the embodiment.
[0080] The above description is only a preferred specific implementation manner of the present invention, and the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.
Claims
1. A method for preparing carbon aerogel, characterized in that: The following steps are involved: (1) Preparation of precursor solution: adding resorcinol and formaldehyde into water to obtain a precursor solution; (2) gelation and aging reaction: subjecting the precursor solution obtained in step (1) to a gelation reaction, and then subjecting the gel to aging to obtain an organic wet gel; (3) Drying the organic wet gel: drying the organic wet gel obtained in step (2) at normal pressure to obtain an organic aerogel; (4) Carbonization treatment: The organic aerogel obtained in step (3) is subjected to carbonization treatment to obtain the carbon aerogel.
2. The method for preparing carbon aerogel according to claim 1, characterized in that: In step (1), the molar ratio of resorcinol to formaldehyde is 1:(1.5-2.5), and the sum of the mass fractions of resorcinol and formaldehyde in the precursor solution is 35-45%.
3. The method for preparing carbon aerogel according to claim 1, characterized in that: In step (1), a catalyst sodium carbonate is also added to the precursor solution, and the amount added is no more than 1 / 2000 of the molar amount of resorcinol.
4. The method for preparing carbon aerogel according to claim 1, characterized in that: In step (2), the gelling and aging temperatures are both 40 to 100° C., the gelling reaction time is 8 to 20 hours, and the aging time is 20 to 60 hours.
5. The method for preparing carbon aerogel according to claim 1, characterized in that: In step (3), the normal pressure drying temperature is 50 to 100° C. and the time is 24 to 48 hours.
6. The method for preparing carbon aerogel according to claim 1, characterized in that: In step (4), the carbonization is carried out under an inert atmosphere, and the specific operation is: heating to 700-1300° C. at a rate of 1-5° C. / min and keeping the temperature for 1-5 hours.
7. A carbon aerogel prepared according to the method for preparing carbon aerogel according to any one of claims 1 to 6.
8. Use of the carbon aerogel according to claim 7 in a supercapacitor.
Citation Information
Patent Citations
High-strength large-size block carbon aerogel and preparation method and application thereof
CN107473199A
Method for preparing carbon aerogel by utilizing normal-pressure drying
CN111498828A
Preparation method of high-temperature-stability SiZrOC aerogel
CN116947045A
Method of manufacturing carbon aerogel and the carbon aerogel manufactured using the same
KR1020090118200A
Carbon aerogels for supercapacitors and method for manufacturing the same
WO2009057902A1